Strategi Pendidik dalam Mewujudkan Pendidikan non Diskriminasi di MTs Terpadu Berkah Palangka Raya - Indah Febrianti; Lia Alviani; Siti Rahmawati; Muhammad Fadhil Huda; Ali Iskandar Zulkarnain (La-Tahzan: Jurnal Pendidikan Islam, 2024)
MTs Terpadu Berkah Palangka Raya is an Islamic educational institution with diverse student backgrounds. In responding to this diversity, an educator must have a strategy to prevent acts of discrimination, so that non-discriminatory education can be realized. This research aims to find out educators' views on non-discrimination education and what educators' strategies are in realizing non-discrimination education at MTs Terpadu Berkah Palangka Raya. The method used in this research is a qualitative method with the research subjects being five educators who are teaching at MTs Terpadu Berkah Palangka Raya. Data collection techniques use interviews. The data that has been collected will then be analyzed using the Miles and Huberman analysis technique, namely collecting data, reducing data, presenting data, and drawing conclusions.The research results show that non-discriminatory education is education that does not discriminate between students either in terms of social status or in terms of intelligence quotient (IQ), so that all students receive the same service and treatment without exception. The strategies used by educators at MTs Terpadu Berkah Palangka Raya in realizing non-discriminatory education are by ta'aruf, following the students' culture, giving questions according to the students' capacity, having the ability to direct students, and providing motivation and advice.